Rancang Bangun Sistem Informasi Manajemen E-Rusunawa Berbasis Websiste : (Studi Kasus di Rusunawa Kaligunting Kab Madiun) - Nanda Rizki Wardana (GLOBAL SCIENTS PUBLISHER, 2025)
Management information systems are very important for managing simple rental flats (Rusunawa). Manual proceses in management often cause inefficiencies and erors.This research aims to design a website-based E-Rusunawa managemnt information system to support administration and information effectively. The method used involves needs analysis, design using UML, and waterfall method development. Results show increased work efficiency and access to information for resident.